The effect of preventive administration of metaraminol on hypothermia and shivering in cesarean section patients randomized clinical trial --a randomized controlled study - Yu, Letao; Zhang, Ziyi; Li, Lili; Shen, Wenzhe; Feng, Qizhu; Lei, Chengwen; Shi, Jun; Li, Rui; Liu, Minghong (Frontiers in Pharmacology, 2025)
BackgroundHypothermia is a common complication during cesarean section and may lead to a series of adverse outcomes. This study aims to evaluate whether prophylactic low-dose metaraminol infusion, compared to saline control, reduces intraoperative hypothermia and shivering in cesarean section patients under spinal anesthesia.MethodsThis study is a randomized, double-blind, placebo-controlled trial, including a total of 66 full-term pregnant women scheduled for cesarean section under spinal anesthesia. Women were randomly divided into the metaraminol (n = 33) and placebo (n = 33). The metaraminol group was given a prophylactic infusion of metaraminol at a rate of 5 mg/h after the start of anesthesia until the end of surgery, while the placebo group was given an equal volume of saline. The primary outcome was the incidence of hypothermia, while secondary outcomes included the incidence of shivering, changes in rectal temperature, neonatal temperature, and the occurrence of hypotension and bradycardia.ResultCompared to the placebo group, the metaraminol group significantly reduced the incidence of hypothermia (54.0% vs. 81.0%, P = 0.017) and shivering (27% vs. 57%, P = 0.012). At the end of the surgery, the rectal temperature in the metaraminol group was significantly higher than that in the placebo group (36.72°C ± 0.31°C vs 36.50°C ± 0.26°C, P = 0.003). In addition, the incidence of hypotension was lower in the metaraminol group compared to the placebo group (6% vs. 24%, P = 0.0039).ConclusionProphylactic infusion of low-dose metaraminol during spinal anesthesia for cesarean section can effectively reduce the incidence of hypothermia and shivering. It has a positive impact on maternal temperature and hemodynamic stability, offering a new and effective strategy for temperature management during cesarean section.